The platelets behaviour in non-alcoholic fatty liver disease. A potential role for antiplatelets drugs?. (25th November 2020) - Baratta, F; Del Ben, M; Pastori, D; Bartimoccia, S; Cammisotto, V; Cocomello, N; Colantoni, A; Pani, A; Nocella, C; Carnevale, R; Angelico, F; Violi, F
Abstract: Background and purpose: Previous studies showed a favorable effect of aspirin, which irreversibly acetylates cyclooxygenase-1 (COX1) so preventing Thromboxane (Tx) A2 biosynthesis, in non-alcoholic steatohepatitis (NASH) and its sequelae. However, the behavior of COX1 in NASH patients is still unknown. Methods: We conducted a cross-sectional study on 44 outpatients with NASH, 50 subjects with simple steatosis (NAFL) and 50 subjects without hepatic steatosis balanced for age, gender and BMI. Serum TxB2, a stable metabolite of TxA2, and urinary 11-dehydro-TxB2, as markers of COX1 activation, plasma soluble P-selectin (sP-selectin), a maker of in vivo platelet activation, serum bacterial lipopolysaccharide (LPS) and serum zonulin, a marker of gut permeability, were measured. Results: Urinary 11-dehydro-TxB2 (p<0.001) and serum TxB2 (p<0.001) levels as well as sP-selectin (p<0.001) were significantly higher in patients with NASH/NAFL compared to the controls (figure 1); the markers of COX1 activation significantly correlated with sP-selectin (p<0.001). Serum LPS was higher in patients with NASH compared with NAFL and controls (p<0.001) and serum zonulin was significantly higher in patients with NASH as compared to controls (p=0.031). A positive correlation (rS=0.37; p<0.001) was observed between serum LPS and serum zonulin. Moreover, serum LPS correlated with serum and urinary 11-dehydro-TxB2 (rS=0.30; p<0.001 and rS=0.61; p<0.001, respectively) and with sP-Selectin (rS=0.32; p<0.001) (figure). At multivariate analysis, LPS above median (OR=3.15, p=0.015) and liver diagnosis (NAFL vs. Controls: OR=6.54; p<0.001 and NASH vs Controls: OR=4.54; p=0.007) were independently associated with sP-selectin above median (table). Conclusions: Patients with NAFLD display enhanced platelet activation, which is associated to COX1 up-regulation. LPS increased by impaired gut permeability may favor platelet activation. Funding Acknowledgement: Type of funding source: None